-4x+9=3x-6

Simple and best practice solution for -4x+9=3x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+9=3x-6 equation:


Simplifying
-4x + 9 = 3x + -6

Reorder the terms:
9 + -4x = 3x + -6

Reorder the terms:
9 + -4x = -6 + 3x

Solving
9 + -4x = -6 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
9 + -4x + -3x = -6 + 3x + -3x

Combine like terms: -4x + -3x = -7x
9 + -7x = -6 + 3x + -3x

Combine like terms: 3x + -3x = 0
9 + -7x = -6 + 0
9 + -7x = -6

Add '-9' to each side of the equation.
9 + -9 + -7x = -6 + -9

Combine like terms: 9 + -9 = 0
0 + -7x = -6 + -9
-7x = -6 + -9

Combine like terms: -6 + -9 = -15
-7x = -15

Divide each side by '-7'.
x = 2.142857143

Simplifying
x = 2.142857143

See similar equations:

| 3x+7=6x+8 | | 3x+6=5x-3 | | 3x+4=-5x-20 | | 3y^2-(5+3y)(y-4)-(10+4y)*2= | | 266-3x=42x+21 | | exp(ln(x))= | | 92-5x=40x+22 | | 3x-8/x=2 | | 92-5x=40x | | 8x^2-50x+72=0 | | -30+27x=11+2 | | 0=2(b^2)+8b+13 | | 4x+2+2=0 | | =3*(-2)-(-5)*(-7) | | =(-7)+(-9)*4 | | =6-3*(-6) | | 2k/k=0.125 | | -9x=13-5x^2 | | -9x=13x-5x^2 | | (5x-1)=10 | | u^2=25 | | 5x/8+2/3=3x/2 | | (7x^2-8)(x-3)=0 | | 8=x*0.04 | | 1^(2/5)/1 | | 95-4x=32x+19 | | x+y-2=5 | | K/K=0.125 | | K^(2/5)=0.125 | | 3v^2+2v-5=0 | | 2x+6=18-10x | | 81-119=-4(-4y)-9(2y)+y |

Equations solver categories